Mechanical Alloying-assisted Coating of Fe–Al Powders on Steel Substrate - Noviyanto, Alfian; Harjanto, Sri; Widayatno, Wahyu Bambang; Wismogroho, Agus Sukarto; Amal, Muhamad Ikhlasul; Rochman, Nurul Taufiqu (UI Scholars Hub, 2020)
The coating layer of Fe–Al powders on the steel substrate was prepared by mechanical alloying at room temperature. Fe, Al, and the steel substrates were milled with high-energy ball milling for 32 h with a ball-to-powder ratio of 8 in an argon atmosphere to prevent oxidation during milling. Although mechanical alloying was performed for 32 h, no new phases were observed after mechanical alloying, as analyzed by X-ray diffraction. However, the crystallite size of the milled powders for 32 h decreased by factor two compared with the initial powders. Scanning electron micrographs showed that the coating layers formed >8 h after mechanical alloying. The intermetallic Fe3Al formed after the substrate was annealed at 500 ℃.